PENGARUH BAURAN PEMASARAN TERHADAP JUMLAH PEMBELIAN PRODUK BAWANG GORENG PADA IKM SAL-HAN - Melinda, Feni; Antara, Made; Effendy, Effendy (AGROTEKBIS, 2018)
This study aimed to determine the Influence of Marketing Mix on the amount of purchasing of fried onion products at Small and Medium Industry (SMI) of Sal-Han. This research was conducted at SMI of Sal-Han in the city of Palu in March up to April 2017. The tool analysis used is multiple linear regressions. The results showed that there is influence of marketing mix consisting of product, price, place and promotion to the amount of purchasing of fried onion product at SMI of Sal-Han.  Variables of product, price, place of distribution significantly are influenced to the number of purchasing of fried onion  product at SMI of Sal-Han, whereas promotion is not significantly affected the amount of purchasing of fried onion product at SMI of Sal-Han.